Analisis Kesesuaian Buku Teks IPA SMP Dengan Kompetensi Dasar Kurikulum 2013 - Median Agus Priadi; Tri Jalmo; Dina Maulina; Sudarto Sudarto (Universitas Lampung, 2022)
This study aims to find out the level of the materials breadth and depth, and misconceptions in the human circulatory system material in science textbooks for SMP class VIII with basic competencies in the 2013 curriculum. This reseacrh use 4 textbooks as a sample that selected by purposive sampling technique. This research is a simple descriptive research. Data collection is done by documentation technique. Data analysis was carried out using descriptive statistical techniques using the percentage formula and described by category level. The results showed that the level of materials breadth in the four textbooks was classified as